The Effect of Facilities and Infrastructure on Learning Experience of Conventional Parasitology Practicum with Distance Method on Students of the Faculty of Medicine Ciputra University - Ridzal Wahid; Hebert Adrianto; Moh. Fawaid (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The Indonesian government issued a policy of Large-Scale Social Restrictions (PSBB) to accelerate the handling of Covid-19. The impact of the Covid-19 outbreak has caused the temporary closure of all educational institutions and face-to-face learning methods in the classroom to distance learning (online). Facilities and infrastructure are one of the important supports in carrying out the learning process. The absence of facilities and infrastructure will complicate learning activities which will also affect the highs and lows of student learning experiences. Because basically, how the course of the learning process will affect how the learning outcomes will be. This research was conducted to determine the effect of facilities and infrastructure on the Parasitology practicum learning experience for students of the medical faculty of Ciputra University. This study uses analytical observation with a cross sectional design with a total research sample of 42 students of the Faculty of Medicine, Ciputra University class of 2018. Data collection was carried out by distributing questionnaires via google form. Data analysis used paired t test. This shows that there is an influence of facilities and infrastructure on the long-distance learning experience of the parasitology practicum of conventional methods.